Genetic diversity of lactic acid bacteria isolated from Sumbawa horse milk, Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Kusdianawati, Mustopa AZ, Fatimah, Budiarto BR. 2020. Genetic diversity of lactic acid bacteria isolated from Sumbawa horse milk, Indonesia. Biodiversitas 21: 3225-3233. LAB from Sumbawa horse milk has good potential antimicrobial and probiotic agents. It is known, the study on LAB diversity based on its phenotypic characters is difficult to be distinguished. However, the development of molecular characterization based on the genotypic characteristic could be done for LAB diversity analysis. The aim of this study is to obtain the genetic diversity of LAB from Sumbawa horse milk collected from Penyaring Village and Lennanguar Village, Sumbawa, West Nusa Tenggara Indonesia. LAB strains were identified based on their genotypic characteristics, including their randomly amplified polymorphic DNA (RAPD) primers profiles and 16S ribosomal RNA (rRNA) sequences. The result of RAPD-PCR analysis showed 5 clusters of dendrograms resulted from GTG5 and LB2 primer amplification. Based on 16 rRNA sequences result, the phylogenetic tree was constructed and revealed 7 species of LAB i.e: SK 1.5, SKP K.3, SKP K.5, SKP K.9/SKP K.7/M.SKP K.3, SKL K.4, M.SKL K.1/ M.SKL K.5, and SKP K.4 belonging to the species of Enterococcus faecium, Weissella confusa, Lactococcus garvieae, Enterococcus thailandicus, Lactobacillus fermentum, Enterococcus faecalis, and Lactococcus petauri. In this study, the bacteria from Enterococcus sp., Lactococcus garvieae, and Lactococcus petauri existed as a novel of bacteria which means they have not been isolated and identified in Sumbawa horse milk compared to the previous findings.
Keywords: 16S rRNA analysis; LAB; RAPD-PCR analysis; Sumbawa horse milk